(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Argumentation is a crucial part of discourse in the scientific field, but is rarely found in the science classroom. This raises the questions of why teachers are not using argumentation, as well as what benefits argumentation provides in the science classroom. Argumentation is not widely used in the science education field due to lack of teacher knowledge about integration techniques and teachers’ fear of unruly class discussions. However, research shows that students benefit in many ways from argumentation based learning by allowing students to work through real world problems to develop higher level thinking skills. This paper discusses the importance of argumentation in science learning, ways to increase argumentation in the science education field, and specific techniques of argumentation that can be implemented in the science classroom.